ASPEK KEBUDAYAAN DALAM PUISI “SELENDANG BATIK IBU” KARYA AMALIA NAJICHAH - Pebriyanti, Firda; Teska, Sanda Amelia; Listiyani, Serly; Julianto, Indra Rasyid (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2025)
The purpose of this research is to describe the aspects of cultural values, and symbols contained in the poem "Selendang Batik Ibu" written by Amalia Najichah, which is in the book of poetry collection "Surat dari Samudra". This study uses a qualitative descriptive method with data collection techniques applied heuristic methods and hermeneutic analysis to understand literary texts in depth. The results obtained in this study are (1) the physical structure in the poem "Selendang Batik Ibu" by Amalia Najichah which is in the poetry collection book "Surat dari Samudra", (2) the inner structure in the poem "Selendang Batik Ibu" by Amalia Najichah which is in the poetry collection book "Surat dari Samudra", (3) Tradition in the poem "Selendang Batik Ibu" by Amalia Najichah which is in the poetry collection book "Surat dari Samudra", (4) Cultural values in the poem "Selendang Batik Ibu" by Amalia Najichah in the book of poetry collection "Surat dari Samudra", (5) Language as a cultural forum in the poem "Selendang Batik Ibu" by Amalia Najichah which is in the poetry collection book "Surat dari Samudra". In the poem "Selendang Batik Ibu" written by Amalia Najichah, which is in the book of poetry collection "Surat dari Samudra" revives traditions and cultural values that are in danger of being lost in this modern era through symbolism and language used, this poem describes the close relationship between the batik tradition as a cultural heritage and the role of mothers in daily life.